THU0288 CANCER RISK IN PATIENTS WITH CUTANEOUS LUPUS ERYTHEMATOSUS AND SYSTEMIC LUPUS ERYTHEMATOSUS COMPARED TO THE GENERAL POPULATION: A DANISH NATIONWIDE COHORT STUDY. (2nd June 2020) - Westermann, R.; Zobbe, K.; Cordtz, R.; Dreyer, L.
Abstract : Background: Research suggesting an elevated risk of cancer among patients with Systemic Lupus Erythematosus (SLE) has increased in recent years. Yet, the size of the overall cancer risk and the risk of respective cancer sites varies. Research examining the cancer risk of Cutaneous Lupus Erythematosus (CLE) patients remains limited. Therefore, in order to further guide and monitor patients with SLE and CLE, additional research estimating the risk of cancer is needed. Objectives: To determine if patients with SLE or CLE have an increased risk of cancer compared to the general population, and furthermore to identify specific cancer types associated with increased risk. Methods: This was an observational cohort study of 3424 SLE and 1886 CLE patients identified in The Danish National Patient Register (DNPR) from 1 st January 1995 to 31 st December 2014. The cohorts were followed up for cancer by linkage to The Danish Cancer Registry (DCR). Based on the age, sex, and calendar specific cancer rates from Denmark, standardized incidence ratios (SIRs) were calculated for the SLE and CLE groups, respectively. Results: The SLE and CLE cohorts were followed for 27, 676 and 13, 048 person years, each group's average duration of follow-up being 8.1 and 6.9 years, respectively. Compared to the general population, the SIRs for the overall cancer (except non-melanoma skin cancer) risk was 1.45 (95%CI 1.30 to 1.62) in the SLE group and 1.35 (95%CI 1.15 to 1.58) in the CLE group. Both CLE and SLE patients had increased risks of hematological, pancreas and lung cancers. Liver, tongue/mouth/pharynx, non-melanoma skin cancer, oesophagus and meninges cancers were only increased in the SLE group. Graphs SLE cancer sites: Standardized incidence ratios and corresponding 95% confidence intervals CLE cancer sites: Standardized incidence ratios and corresponding 95% confidence intervals Conclusion: The risk of overall cancer was significantly increased in patients with SLE and CLE. Hematological, pancreas and lung cancers were elevated in both groups, while certain virus-associated cancers and other sites were increased only among SLE patients. Awareness of cancer in patients with SLE and CLE should be considered, especially of symptoms from high-risk sites. Disclosure of Interests: None declared